(untitled) (Asian Journal of Pharmaceutics (AJP), 2015)
The purpose of present research work was to develop spray-dried mucoadhesive microspheres of prochlorperazine (PCPZ)Â for intranasal administration with an aim to avoid first-pass metabolism and to improve therapeutic effectiveness. A 23Â factorial design was employed with amount of polymer, feed flow rate and volume of gluteraldehyde as independent variablesÂ while particle size of the microspheres and percentage drug entrapment efficiency as dependent variables.The microspheresÂ were evaluated for drug loading, surface morphology, degree of swelling, in-vitro mucoadhesion, drug release, histopathologyÂ and stability studies. Particle size of all batches was found to be in the range of 7.32â€“15.67 Î¼m. The percentage entrapmentÂ efficiency was found to be in the range between 84.90 and 96.21. In-vitro mucoadhesion was performed by adhesion numberÂ using goat nasal mucosa and was observed in a range from 76.25 to 87.72. The optimum formulation was selected basedÂ on the criteria of attaining the minimum value of particle size with substantial entrapment efficiency. Scanning electronÂ microscopy analysis of the microspheres revealed that the microspheres were nearly smooth and spherical. In-vitro diffusionÂ studies showed non-Fickian drug release.The Fourier transform infrared spectrophotometer spectra revealed no interactionÂ between drug and excipients. Optimum formulation was found to be nonirritant in histopathology study carried out on goatÂ nasal mucosa. The prepared microspheres were found to be stable over a period of 3 months even after stored at 40Â°C. InÂ conclusion, PCPZ loaded mucoadhesive chitosan microspheres were reported for the first time, being suitable for intranasalÂ delivery for the treatment of nausea and vomiting. Key words: Chitosan, factorial design, nasal drug delivery, prochlorperazine, spray drying